GROWTH AND PRODUCTION OF VARIOUS WHEAT GENOTYPES AT VARIOUS PEG CONCENTRATION IN HYDROPONIC - Muh. Farid Bdr (Universitas Sembilanbelas November Kolaka, 2018)
Wheat is a sub-tropical cereal that can be planted in the tropics, on the highland with altitude 1000 m asl. The development of wheat in the highlands compete with horticultural crops, so the creation of tropical wheat that is adaptive to lowland and drought tolerance is an alternative problem-solving. The aims of this study is to test the generation and to screen three type of mutant that is adaptive in lowland with high temperature. The study was conducted at Tamalanrea Jaya, Tamalanrea regency, Makassar province from May to August 2017. The research was conducted on hydroponic media in the plastic house (green house) at altitude 800 m asl with an average temperature of 28oC (morning) and an average temperature of 33oC (afternoon). The study was used split-plot design with the main plot of polyethylene glycol (PEG), ie 0%, 5%, 10%, and 15%; the plot was 15 wheat genotypes. The results showed that the addition of PEG concentrations at 5%, 10% and 15% decreased the crop yield by 35.91%, 55.63%, and 71.83%. Adaptive and potential genotypes developed in lowland with dry climatic conditions are genotype N.200 2.4.B.6 and genotype N.300 4.3.6